Pengaruh Penerapan Audit Syariah Pada Peningkatan Kepercayaan Publik (studi kasus di lembaga Amil zakat) - Muhammad Ardi/ Rusti Rahayu - (IQTISHADUNA, 2018)
This study aims to find out how the influence of the implementation of sharia audits and increasepublic beliefs and analyze the implementation of sharia audits of increasing public trust in the Amil Zakat paper method institute. This is used is a descriptive method and verification method approach. Writing this article is a quality article. This paper is a library research, with literature-literary reviews related to the topic of writing this paper. Analysis of the paper data used is content analysis. The results of this study indicate that there is a positive and strong relationship between sharia audit practices and increasing public trust.